A Soluble Diketopyrrolopyrrole Derivative and Its Applications for Organic Phototransistors. Issue 11 (11th October 2018) - Lee, Chulyeon; Kim, Joonwoo; Moon, Yejin; Kim, Dohan; Song, Dong‐Ik; Kim, Hwajeong; Kim, Youngkyoo
Abstract: A small molecular diketopyrrolopyrrole (DPP) derivative containing 2, 4‐difluorinated phenyl groups, 3, 6‐bis(5‐((E)‐2, 4‐difluorostyryl)thiophen‐2‐yl)‐2, 5‐bis(2‐ethylhexyl)‐2, 5‐dihydropyrrolo[3, 4‐c]pyrrole‐1, 4‐dione (EHD2FV), was synthesized by a cross‐coupling reaction with 90% yield. The solid EHD2FV film exhibited a broad optical absorption up to 1000 nm, it featured a deep‐lying LUMO energy (4.49 eV). EHD2FV was employed as an electron acceptor (n‐type) for bulk heterojunction (BHJ) layers, which act as a sensing channel layer in organic phototransistors (OPTRs), while poly(3‐hexylthiophene) (P3HT) was introduced as an electron donor (p‐type). The OPTRs with the P3HT : EHD2FV BHJ layers were capable of sensing a deep red light (700 nm). The results showed that the best photosensing performance (photoresponsivity=337.1 mA/W) was achieved at the EHD2FV molar ratio of 0.05. Abstract : A soluble DPP derivative with 2, 4‐fluorinated phenyl groups, EHD2FV, was synthesized and applied as an electron‐accepting sensing molecule in deep‐red‐light‐detecting organic phototransistors with bulk heterojunction (P3HT : EHD2FV) sensing channel layers.